Relation between Ocean Literacy and Science Learning Outcomes of Class IX SMPN 04 Keruak, Lombok Timur 2022 - Ummi Auliya’ Amalina; Karnan Karnan; Tri Ayu Lestari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Ocean has abundant resources which if we manage properly, can support the sustainability of life and ecosystems. Managing the ocean requires good ocean literacy. Ocean literacy is knowledge about the sea. Ocean literacy needs to be developed in a learning system to increase the next generation's knowledge about the sea. In addition, science learning outcomes are important to know as a measure student's mastery of science to understand natural phenomena both land and sea, it is also important to see how the relationship between ocean literacy and science learning outcomes. This study aims to see how the level of student's ocean literacy, science learning outcomes, and how the relationship between ocean literacy and science learning outcomes at SMPN 4 Keruak. The results showed that the literacy level of class IX students at SMPN 04 Keruak was 24.49 then the results percentaged to 24% which was very low. Student learning outcomes obtained an average of 34.1 in the low category, no students had scores above the standard point so that the value P more than 59. The relationship between ocean literacy and learning outcomes obtained a significant correlation value of 0.065 which is not correlated with a correlation coefficient of 0.240 which has a weak correlation. If viewed from the significance value, it is not correlated because the value obtained is greater than the rtable, but the difference is very small, it is just 0.01 so that when viewed from the correlation coefficient it can be categorized as weakly correlated, not uncorrelated at all